"I am Peru": Literature Nobel - Nizama Valladolid, Martin (2010)
The route of life of insigne is reviewed writer, politician, free thinker, democrat and humanist, analyze elements than sufficient more they catalogue that it like Peruvian a universal one, a human being full of generosity. One becomes remember of the unforgettable moments from the announcement of the concession of the prize, in the Cervantes Institute of New York; soon the moment at which king Carlos XVI Gustavo of Sweden gave, the Nobel prize of Literature 2010 to Mario Vargas Llosa (MVLl) in the Concert hall of Stockholm. MVLl in its speech of gratefulness in New York, showed before the international press that the prize was an award to the Spanish language and displayed the best thing of its erudition in a full speech of emotions and expressed its peruanity to everybody with a statement that will be unforgettable: "PERU I AM". Expressions from greatness and gratefulness to their country, in which the flaming Nobel prize of 74 years synthesized its deep peruanity, and with which it filled of pride approximately to 30 million of Peruvian, thirsty of transcendental triumphs. Its origin arequipeño, its familiar surroundings, its childhood, childhood and adolescence in Cochabamba, Piura and Lima are analyzed; the conflicting relation with its father, its adolescence in the Military School Leoncio Prado, where its literary vocation began; these experiences evoked in its autobiographical book "the Fish in the Water"; soon its telluric roots, its passage by the Greater National University of San Marcos, where it began to publish his first stories. Also, his consecrated life in favour of the fight by the civil freedom, rights and the human rights and their incursion in the peruvian politic is approached. Finally, a finishing touch describing to the human MVLl, its deep sensitivity, expression of love to the freedom, its inexhaustible creative capacity, its ideological thought, and its certainly, to give account us that we are in front of an ecumenical humanist.